Pelatihan Membaca Kritis Dengan Media Pembelajaran Cerpen - Astari Amalia Putri; Tutut Sumartini; Sinta Oktaviani Safitri; Malika Sharma; Rusti Junia; Riske Nurfardiyanti; Fahira Fahimna; Akbar Nugroho (Jurnal Nusantara Berbakti, 2023)
Government data shows reading comprehension and analysis level of Indonesian citizens is still very low. As a result, there are many Indonesians who read words as they are without understanding what they mean. This is a concerning fact, as humans grow older, humans should become more accustomed to critical thinking: analyzing something from what is implied. Critical thinking is closely related to critical reading as critical reading means reading while analyzing the text. This critical reading training was offered by our PKM team for Al-Ghozali High School students, Bogor. Our team also found out that those students had more problem: they are not familiar with English even though English is an obligatory language in that boarding school. After considering the problem, two English short stories were chosen for the implementation of this PKM. The training was carried out using presentation activities on critical reading, reading activity, and group discussion, as well as pre-test and post-test. The results show that an in-depth presentation on how to make responds in relation to critical reading and reading short stories in English can foster critical thinking and increase English vocabulary for students.